Pengaruh Metode Bermain Peran terhadap Hasil Belajar Bahasa Indonesia Siswa - Cahayatul Aulia; Siti Rohana Hariana Intiana; Muhammad Tahir (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The role playing method was one alternative that can be used in the learning process in the classroom. The purpose of this study was to determine the effect of the role playing method on learning outcomes in Indonesian Languange subjects for fifth grade students of SDN 2 Lendang Kunyit in the 2021/2022 academic year. The method used in this study was a pre-experimental method with a one-group pretest-posttest research design. The research was conducted at SDN 2 Lendang Kunyit, Central Praya, NTB. The sample of this study were all students of class V, totaling 30 students. Data collection techniques were observation, documentation and student learning outcomes. Data analysis used statistical test analysis with the help of SPSS version 25.00. The conclusion of this study that there was an effect of the role-playing method on the learning outcomes of fifth graders at SDN 2 Lendang Kunyit in the 2021/2022 academic year. This was proved by the results of the t-test Sig. (2-tailed) 0.000 <0.05, which means that there was an influence of the learning method by role playing. The use of this method can improve students' Indonesian learning outcomes. Therefore, it was recommended to use this method for teaching other materials.